Anemia and metabolic acidosis are a predictor for mortality in children with severe acute malnutrition at Sanglah General Hospital, Bali - Ni Putu Andina Kluniari; I Gusti Lanang Sidiartha (Intisari Sains Medis, 2020)
Background: Severe acute malnutrition (SAM) is one of the leading causes of morbidity and mortality in children in developing countries.Â  Nutritional disorders are frequent in hospitalized patients, of which malnutrition is the most prevalent Anemia and PH disturbance was commonly found in this condition. This study aims to determine the association between anemia and metabolic acidosis with the mortality among children with severe acute malnutrition.Methods: A retrospective cohort study was conducted among 135 severe acute malnutrition children in the pediatric care unit of Sanglah General Hospital from the 2017-2018 period. The inclusion criteria were children aged 1 month to 18 years diagnosed with SAM. Exclusion criteria were a patient diagnosed with a hematological disorder or renal disorder. Data were analyzed using SPSS version 20 for Windows.Results: Anemia was diagnosed in 89 (65.9%) subjects in this study. Anemia increases the risk of death significantly by 3.98 times (95% CI 2.167-10.389; p<0.001). Metabolic acidosis was found in 35 (25.9%) subjects; this condition was also shown to significantly increase the risk of death by 1.5 times (95% CI 1.005-2.145; p=0.018).Conclusion: Anemia and metabolic acidosis can be used as predictors for mortality in severe acute malnutrition patient significantly.